The Influence of Dividend Policy, Liquidity, Company Size, and Company Growth on Debt Policy in Manufacturing Companies Listed on the Indonesian Stock Exchange (BEI) - Elisabeth, Cherly (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to determine the effect of Dividend policy, Liquidity, Company Growth, and Company Size on Debt Policy in Manufacturing Companies listed on the IDX (Indonesia Stock Exchange). This research method used is quantitative method. This research is secondary data whose data is quantitative. Quantitative data in this study were obtained from the annual financial statements of each company and the Indonesian Capital Market Directory (ICMD) during the research period obtained from www.idx.co.id. The results of this study based on the analysis show that Dividend Policy has a positive and significant effect on debt policy in Manufacturing Companies listed on the IDX. Liquidity has a positive and significant effect on debt policy in Manufacturing Companies listed on the IDX. Company size has a negative and significant effect on debt policy in Manufacturing Companies listed on the IDX. Company Growth has a negative and significant effect on debt policy in Manufacturing Companies listed on the IDX.